Some blood biochemical as indicator to improve productive and reproductive performance in rabbit population - El Darawany A.A.; Farghaly H.M. (2. International Conference on Rabbit Production in Hot Climates, 1999)
Genetic and environmental factors that influence serum and urine progesterone (SP and UP) and blood protein patterns were evaluated for 686 Bauscat does from 117 dams and 34 sires. The sire and dam within sire effects were significant for most blood traits. Progesterone was detected by RIA in fresh urine after conversion from pregnadiol to progesterone. The heritability (h2) for SP and UP at different periods of gestation were moderate. Gestation period (GP) showed negative highly significant genetic correlations (rG) with each of SP, UP, Alb, Alb/Glo ratio and negative correlations with NEP11 and Glo. Litter size and weight at birth (LSB and LWB) showed positive rG with each of SP, UP15, TP and Alb and negative rG with NEP11. The rG were negative between bunny weight at birth (BWB) and all progesterone and protein patterns. Genetic improvements of fertility based on progesterone and blood protein patterns in doe rabbits would be 41 per cent or more as efficient as indirect selection. It was concluded that the h2 were sufficiently high to permit selection on individual levels for some of the biochemical traits in doe.
2. International Conference on Rabbit Production in Hot Climates, 1998/09/07-09, Adana (Turkey)